Financial Accounting, An Introduction to Concepts, Methods, and Uses (Book). - Arnold, Donald F.; Meyer, Philip E. (The Accounting Review, 1983)
Reviews the book "Financial Accounting: An Introduction to Concepts, Methods, and Uses," 3rd ed., by Sidney Davidson, Clyde P. Sticney and Roman Weil.